POTENSI DAN STRATEGI PENGEMBANGAN PETERNAKAN AYAM KAMPUNG DI KOTA PADANG PROVINSI SUMATERA BARAT - Fikya Juanda Fikya Juanda; Arfa'i; Husmaini (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2023)
Food independence is a reference for a country in solving various problems related to the availability of the necessities of life for people who do not depend on other countries, especially the livestock sector. Prioritizing the development of local livestock such as native chickens as producers of food products of animal origin, able to answer challenges in the world of animal husbandry as it is today. This study aims to: (1) conduct an analysis of the factors that influence the development of free-range chicken in the city of Padang, (2) provide an alternative strategy based on the potential of the city of Padang for a better free-range chicken development effort. This research was conducted by conducting surveys and direct observations at the research site. The research was carried out in three stages: 1) Identifying and analyzing external factors from the free-range chicken development effort, 2) Identifying and analyzing the internal factors of the free-range chicken development business, and 3) Creating alternative strategies for the development of free-range chicken livestock in the city of Padang. From the results of the study, it is known that the city of Padang has a carrying capacity index of 9.2 which means that it is included in the category of good carrying capacity for the development of free-range chicken businesses. Keywords: Strategy, Native Chickens, Carrying Capacity Index